The Effect of a Auditor Competence and Independence on Audit Judgment with Audit Fee as a Moderating Variable - Novita Wulandari; Radina Amalia (Journal of Accounting and Auditing, 2025)
Purpose - This study aims to obtain empirical evidence about the effect of Auitor Competence and Independence on Audit Judgment with Audit Fee as a Moderating Variable. Design/methodology/approach - The esearch uses a type of quantitative research. This research was conducted using a questionnaire that sent an email to a public accounting firm to be filled in by auditors who work in public accounting firms registered with the Ministry of Finance, namely 448 Public Accounting Firms (KAP). From the distribution of these questionnaires, 119 Public Accounting Firms (KAP) located on the island of Java were willing to provide answers. Of the 50 Public Accounting Firms, 30 auditors filled out the questionnaire with the provisions of 1 questionnaire given with 30 questions. To get the results of this study, researchers used PLS SEM version 3.0. Findings - The results of this study found that Auditor Competence has a positive and statistically significant effect on audit judgment, and Independence has a positive but statistically insignificant effect on audit judgment, As for other findings, audit fees weaken the relationship between Auditor Competence and audit judgment, and audit fees strengthen the relationship between Independence and audit judgment. Research limitations/implications  - This study focuses on the factors that influence audit judgment. This study adds audit fees as a moderating variable and to the best of the author's knowledge, the author believes that this study presents the latest evidence of audit fees as a moderating variable focused on auditors who work in public accounting firms registered with the Ministry of Finance. Keywords : Audit Competence, Independence, Audit Judgment, Audit Fee